"A German Bred Revolt": the Manchester Guardian's perceptions of the Irish Easter Rising, 1916. Issue 4 (2nd October 2019) - McMorran, Kieran
ABSTRACT: At the time of the Easter Rising of 1916 Britain had been engaged in the Great War against Germany for almost two years and on a scale and intensity previously unprecedented. This broader Great War backdrop is significant when analysing the 1916 Easter Rising, as it not only influenced the events which occurred in Dublin, but also the interpretation and presentation of the political violence. Despite the Easter Rising being well-documented in secondary literature, with a resurgence accounted for by its recent centenary, the British press and its portrayals of the events of 1916 has been one aspect which has not received as much scholarly attention. By analysing key stages in the uprising's portrayal, it can be determined that the Manchester Guardian 's utilisation of the German connection had a two-fold implication. Utilising historical precedents of German-Irish "friendship", such as the gun-running episodes of pre-War 1914, the newspaper justified its portrayal of Germany provoking violence in Ireland to disrupt British war efforts. Additionally, for the Manchester Guardian, the Irish rebels were depicted negatively in its articles as it attempted to halt the growth of republicanism, thereby ensuring the promotion of a more "moderate" form of nationalism.